The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ffj.3343
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Croton argyrophyllus essential oil on behavioural models of nociception

Abstract: Croton argyrophyllus Kunth (Euphorbiaceae) is a shrub abundant in the northeast region of Brazil where it possesses ethnobotanical use. To assess the antinociceptive action of C. argyrophyllus, studies were conducted in behavioural models of nociception, and some of the mechanisms given under this effect investigated. The essential oil (EO) of C. argyrophyllus leaves (10, 30 and 100 mg/kg) was used in mice via the oral route in both the chemicals (acetic acid, formalin, capsaicin and glutamate) and thermal noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…In a previous study conducted with the Croton rhamnifolioides species, this was shown to possess gastroprotective effects involving the opioid system and the nitric oxide pathway [5], which are results that corroborate with our study. Some studies investigating the possible mechanisms of action involved in the antinociceptive response with species from the Croton genus, such as those using the Croton conduplicatus [57] and Croton argyrophyllus Kunth [58] essential oils, also support our research. Moreover, a previous study described the anti-inflammatory effect of the OEFC [3] and COEFC [16], which are results that corroborate with the antinociceptive action observed in the present study, since pain is a classic sign of the inflammatory process.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study conducted with the Croton rhamnifolioides species, this was shown to possess gastroprotective effects involving the opioid system and the nitric oxide pathway [5], which are results that corroborate with our study. Some studies investigating the possible mechanisms of action involved in the antinociceptive response with species from the Croton genus, such as those using the Croton conduplicatus [57] and Croton argyrophyllus Kunth [58] essential oils, also support our research. Moreover, a previous study described the anti-inflammatory effect of the OEFC [3] and COEFC [16], which are results that corroborate with the antinociceptive action observed in the present study, since pain is a classic sign of the inflammatory process.…”
Section: Discussionsupporting
confidence: 78%
“…Estudos realizados já demonstraram que C. argyrophyllus produz óleo essencial, apresentando algumas atividades biológicas, como a atividade inseticida sobre larvas e adultos de Aedes Aegypti (CRUZ et al, 2017), o efeito antiinflamatório e antioxidante (RAMOS et al, 2013), o efeito antinociceptivo (RAMOS et al, 2016) e a atividade citotóxica (ARAÚJO et al, 2014). Entretanto, estudos relacionados com a atividade antioxidante e os teores de fenólicos e flavonoides totais dos extratos vegetais ainda não foram encontrados.…”
Section: Introductionunclassified
“…Generally, the major constituents are responsible for the biological activities of essential oils extracted from different aromatic species. 13,55 In this context, the biological activities of C. argyrophyllus essential oil reported by TA B L E 4 Chemical composition of C. argyrophyllus essential oil obtained by hydrodistillation using the following samples: Fresh leaves without enzymatic pretreatment (FL 0 ), fresh leaves with enzymatic pretreatment (FL ept ), and dried leaves without enzymatic pretreatment (DL) several authors [11][12][13][14] may be attributed to high concentrations of bicyclogermacrene, β-caryophyllene, spathulenol, and α-pinene, the major constituents in those studies and in the present one.…”
Section: Chemical Analysis By Gc-msmentioning
confidence: 99%
“…The C. argyrophyllus essential oil has promising active components for the development of drugs and botanical insecticides. [11][12][13][14] Therefore, the search for new methodologies capable of maximizing the extraction yield of these…”
Section: Argyrophyllus (%) Cmentioning
confidence: 99%
See 1 more Smart Citation